Bicoloratum Dai and Li, a new synonym of the leafhopper genus Scaphoideus Uhler (Hemiptera, Cicadellidae, Deltocephalinae), with description of two new species - Chen, Fangying; Dai, Wu (Zootaxa, 2015)
Bicoloratum Dai and Li, 2011 is considered to be a junior synonym of Scaphoideus Uhler, 1889 based on study of specimens of two new species, one of which is morphologically very similar to the type species of Bicoloratum, B. pintungisis Dai and Li 2011. Three valid species now included within the genus Scaphoideus are: S. dinghuensis sp. nov., S. taishanensis sp. nov. and S. pingtungisis (Dai and Li, 2011) n. comb. The detailed morphology of the two new species is described, and photographs of their external habitus and male and female genitalia are also given.